2013
DOI: 10.1111/ceo.12139
|View full text |Cite
|
Sign up to set email alerts
|

Heparanase‐1 and components of the hedgehog signalling pathway are increased in untreated alveolar orbital rhabdomyosarcoma

Abstract: Both heparanase-1 and hedgehog signalling pathway are involved in the pathogenesis of alveolar orbital rhabdomyosarcoma; however, chemotherapy and/or radiotherapy appears to significantly inhibit their upregulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Recent evidence has shown that the abnormal activation of the hedgehog (Hh) signaling pathway is prevalent in ARMS tumors (5)(6)(7). Arsenic trioxide (ATO), a Food and Drug Administration (FDA)-approved drug, was discovered through advanced research methods and was shown to be clinically useful against tumors exhibiting activated Hh signaling.…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence has shown that the abnormal activation of the hedgehog (Hh) signaling pathway is prevalent in ARMS tumors (5)(6)(7). Arsenic trioxide (ATO), a Food and Drug Administration (FDA)-approved drug, was discovered through advanced research methods and was shown to be clinically useful against tumors exhibiting activated Hh signaling.…”
Section: Introductionmentioning
confidence: 99%